Tackling Emissions and Food Security in East Africa through Improved Animal Health - Arndt, Claudia; Bronsvoort, B.M. de C.; Cook, Elizabeth A.J.; Cramer, Laura K; González Gordon, L; Gurmu, Endale Balcha; Knight-Jones, Theodore J.D.; Lanzoni, L; Özkan, Şeyda; Rosenstein, Peri K; Ruegg, Pamela; Temesgen, Wudu; et al. (International Livestock Research Institute, 2025)
Presented at the Global Climate-Smart Agriculture Conference (Brasília, November 2025), this talk highlights how improved animal health reduces greenhouse gas emissions, enhances productivity, and improves food security in East Africa. Using data from Kenya, Ethiopia, and Tanzania, the team demonstrates that reducing disease prevalence—such as East Coast fever, mastitis, and parasitic infections—lowers emission intensity while boosting resilience and animal welfare. The presentation also outlines ongoing efforts to embed animal-health metrics within Kenya’s national climate and livestock policies, advancing cross-sector integration for sustainable, low-emission livestock systems.